COMPUTATIONAL THINKING AS A PEDAGOGICAL TOOL FOR UKRAINIAN STUDENTS - Kush, Joseph C. (Професіоналізм педагога: теоретичні й методичні аспекти, 2019)
The article focuses on the importance of developing computational thinking of Ukrainian students and the ways computational thinking can be integrated into the curricula of higher educational institutions. The incorporation of enhanced pedagogy into the educational curricula is particularly needed in countries such as Ukraine which is currently undergoing strategic modernization and reform. The author defines the concept of computational thinking as it is used in constructivism learning theory and social-constructivism theories. It is emphasized in the article that computational thinking reduces complex problems into smaller and more manageable problems, which make it easier to solve either using a computer or without technology. A wide range of researches conducted by the scientists all over the world are presented. The aim of the article is to analyse the implementation of computational thinking as a pedagogical tool for Ukrainian educational system. The special attention is paid to developing computational thinking of children at an early age. Pattern Recognition is considered to be one component of computational thinking and can be used to teach the process of searching for trends, similarities, differences, or regularities. The computational thinking instructions can be carried out in the area of the computer science or outside of computer science. Students who learn computer-programming skills as part of a have been shown to experience numerous benefits to their education because computational thinking is a problem-solving skill for all disciplines that can be taught through the integration into a particular content area or alternatively by teaching it as a stand-alone content area. The author recommends Ukrainian educators to consider the integration of unplugged CT activities into their lesson plans. Unplugged curricular activities are implemented without the use of computers and are typically considered as an important first step toward comprehensive CT integration. Unplugged experiences are claimed to serve as a foundational in learning CT because they typically require the least amount of technical knowledge.